(untitled) (Medical Forum Monthly, 2024)
Objective: To find histopathologic and clinicopathologic correlations in children with atypically presented nephrotic syndrome. Study Design: Retrospective observational study Place and Duration of Study: This study was carried out at the Department of Paediatric Nephrology, Children's Hospital & Institute of Child Health, Multan, Pakistan from December, 2005 to January, 2014. Materials and Methods: Medical record and the biopsy reports of 80 children (age 1-15 years) with nephrotic syndrome, who had atypical features at presentation and had a renal biopsy, were analyzed. Atypical features included hypertension, gross hematuria, hypocomplementemia, impaired renal function, and age more than 12 years, or manifestation of other systemic diseases in children. Results: Overall results showed hypertension as the commonest (90%) atypical feature followed by impaired renal function (65%), atypical age (53.7%), gross hematuria (41.3%), and hypocomplementemia (31.3%). Histopathologic reports revealed non-MCD lesions in 76 (95%) cases. The commonest lesion was FSGS (25%) followed by MesPGN (23.8%), MCGN (17.5%), and LN (12.5%). Out of the total 80 patients, 62 were idiopathic atypical nephrotic syndrome cases and 18 were secondary (due to some underlying systemic cause) nephrotic syndrome cases. Secondary causes, in decreasing frequency, included lupus nephritis/nephrosis (LN) (n=10; 55.5 %), hepatitis B virus associated nephrosis (HBVAN) (n=4; 22.2%), Henoch Schonlein Purpra nephritis/nephrosis (HSPN) (n=2; 11.1%), hepatitis C virus associated nephrosis (HCVAN) (n=1; 05.5%), renal amyloidosis (RA) (n=1; 05.5%). Conclusion: Renal biopsy done at the onset of atypically presented nephrotic syndrome provides useful guidance to the final diagnosis. Non-MCD lesions predominate. Some secondary nephrotic syndrome patients also present as atypical nephrotic syndrome; further clinical and laboratory evaluation reveals the secondary cause.